COMMERCIAL AND LOGISTICS ACTIVITIES IN THE DIGITAL CONTRACT-TYPE ECONOMY - HAVENKO, Mykhailo; SHARKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The modern world has already taken the first step towards a fundamentally new technological, economic and social reality. However, it is difficult to overestimate the challenges facing modern industrial society. We are talking about a change in the global socio-technological structure, the consequence of which is a complete reformatting of the systems we are used to, the formation of new social and economic strategies. At the same time, the technological paradigm is changing, management models and social norms are changing, there are large-scale demographic shifts caused by the state of war in Ukraine, etc.For domestic logistics, in the conditions of martial law, established supply chains ceased to function. Closed ports, lack of air connections, risks associated with road transport - enterprises with well-established logistics were forced to change positions within a few days. The realities of the war imposed restrictions on all spheres of life, but primarily on supply and communication. The danger of using transport, the risk of losing goods during warehouse storage, the need to rebuild routes directly during movement - this is only a small part of what logistics faces during war. Because of that, it is worth optimizing processes and adapting to the external environment, or admit the impossibility of carrying out economic activities by the enterprise.The work provides an updated scientific interpretation of the synergy of commerce and logistics in the modern conditions of digitalization of the contract economy. The peculiarities of the manifestation of synergy are revealed from the example of the organization of the smart contracting system of the enterprise's transport and logistics business. The essential characteristics and rules of operation of the system are described with the aim of achieving the synergy effect in its qualitative and quantitative forms. An algorithm for substantiating project decisions regarding the creation of a smart contracting system based on the application of a problem-situational approach, which forms the structure of the road map for project implementation, is proposed.
Keywords: contract economy; digital economy; tensor; transport and logistics business; smart contracting system; synergy effect of the smart contracting system; problem-situational approach